FEMTOSECOND-ASSISTED DEEP ANTERIOR LAMELLAR KERATOPLASTY FOR KERATOCONUS: CONTEMPORARY CLINICAL PERSPECTIVES AND OUTCOME ANALYSIS - Karimova M.Kh., Inomzhonova M.I., Abdullaeva S.I., (Central Asian Journal of Medicine, 2025)
Femtosecond-assisted deep anterior lamellar keratoplasty (femto-DALK) represents a contemporary surgical approach for corneal pathologies that preserves the recipient's endothelium. Despite increasing clinical adoption, comprehensive analysis of femto-DALK advantages over conventional techniques requires further investigation. We conducted a retrospective analysis of 12 patients aged 18-42 years with stage III keratoconus who underwent femto-DALK between 2023-2024. Primary outcome measures included visual acuity, refractive outcomes, keratotopographic parameters, and healing characteristics. Best-corrected visual acuity of 0.6 or better was achieved in 66.67% of patients at 12 months post-operatively, with mean postoperative astigmatism of 2.1±0.9 D. Tissue interface precision was characterized by predictable residual stromal thickness of 15.6±5.3 um. Big-bubble formation was successful in 91.7% of cases, with conversion to penetrating keratoplasty required in only 8.3% of procedures. Postoperative complications were minimal, with complete anatomical apposition of Descemet's membrane confirmed by OCT in all cases. Femto-DALK demonstrates significant advantages in tissue interface precision and accelerated wound healing compared to conventional keratoplasty techniques, confirming high efficacy in achieving stable visual and refractive outcomes with enhanced surgical predictability.